2019
DOI: 10.1017/s1092852918001633
|View full text |Cite
|
Sign up to set email alerts
|

Demoralization in essential tremor: prevalence, clinical correlates, and dissociation from tremor severity

Abstract: Objective.Essential tremor (ET) is associated with psychological difficulties, including anxiety and depression. Demoralization (feelings of helplessness, hopelessness, inability to cope), another manifestation of psychological distress, has yet to be investigated in ET. Our objectives are to (1) estimate the prevalence of demoralization in ET, (2) assess its clinical correlates, and (3) determine whether demoralization correlates with tremor severity.Methods.We administered the Kissane Demoralization Scale (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 71 publications
(133 reference statements)
3
9
0
Order By: Relevance
“…However, there are some controversial findings. Other studies have reported that demoralization (ie, depression) or cognitive deficits are not related to tremor severity, indicating that they are separate comorbid entities 38 . Additionally, Matteo et al 8 reported a high prevalence of axis I disorders in patients with ETh, indicating that ET manifests psychiatric disorders, especially axis I disorders.…”
Section: Discussionmentioning
confidence: 97%
“…However, there are some controversial findings. Other studies have reported that demoralization (ie, depression) or cognitive deficits are not related to tremor severity, indicating that they are separate comorbid entities 38 . Additionally, Matteo et al 8 reported a high prevalence of axis I disorders in patients with ETh, indicating that ET manifests psychiatric disorders, especially axis I disorders.…”
Section: Discussionmentioning
confidence: 97%
“…The disease can be either a component of different neurodegenerative diseases or an isolated disease. (18) The molecular mechanism of ET is still unclear because there is no specific diagnostic marker for ET. The disease has clinical similarities with some diseases such as dystonia and Parkinson's disease (PD) and can also be seen together with other neurological diseases such as restless leg syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…One-way ANOVA results (GRF corrected with a voxellevel P < 0.01 and a cluster-level P < 0.05, gray matter mask, estimated smoothing kernel with FWHM: 6 × 6 × 4 mm3 and cluster size > 405 mm 3 ) showed ReHo changes in the prefrontal cortices, anterior cingulate cortices, motor cortices, insular cortices, superior parietal lobules, superior temporal cortices, cuneus and cerebellum among the three groups (Fig. S1).…”
Section: Local Fc Changes Among the Three Groupsmentioning
confidence: 99%
“…S1). Figure 1 shows the post hoc two-sample t-test results (GRF corrected with a voxel-level P < 0.001 and a cluster-level P < 0.05, ANOVA results as mask, estimated smoothing kernel with FWHM: 6 × 6 × 4 mm 3 and cluster size > 432 mm 3 ). Compared with the HCs, the depressed ET patients had increased ReHo in the bilateral precentral cortices, supplementary motor cortices, superior and middle prefrontal cortices, anterior cingulate cortices, insular cortices, superior parietal lobules, cuneus and right superior temporal cortex, and decreased ReHo in the bilateral cerebellum lobules IV-V, cerebellum lobules VI, cerebellum lobules VIII, cerebellum lobules IX, cerebellum lobules crus 1 and left superior temporal cortex.…”
Section: Local Fc Changes Among the Three Groupsmentioning
confidence: 99%
See 1 more Smart Citation